Psychological and pedagogical conditions for the formation of professional subjectivity of future teachers - Tatiana V. Dmitrochenko (Russian Journal of Education and Psychology, 2025)
Background. Modern documents regulating state policy in the field of education (the national project "Youth and children", the national project "Personnel", etc.), as the priority goals of the national development of the Russian Federation put forward the improvement of the process of professional training of future specialists. In this regard, the problem of training a competitive specialist in the field of education, who is able to efficiently and effectively implement professional and pedagogical functions in practice, becomes urgent.